Land-Rich Economies, Education and Economic Development - Sebastian Galiani; Daniel Heymann; Carlos Dabus; Fernando Tohme (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2007)
We analyze the emergence of large-scale education systems in a framework where growth is associated with changes in the con guration of the economy. We model the incentives that the economic elite could have (collectively) to accept taxation destined to nance the education of credit-constrained workers. Contrary to previous work, in our model this incentive does not necessarily arise from a complementarity between physical and human capital in manufacturing. Instead, we emphasize the demand for human-capital-intensive services by highincome groups. Our model seems capable to account for salient features of the development of Latin America in the 19th century, where, in particular, land-rich countries such as Argentina established an extensive public education system and developed a sophisticated service sector before starting signi cant manufacturing activities.
Keywords: N36; O12; I2; 330